Myeloma patients’ attitudes and perceived burden of treatment administration routes and locations: insights from a pan-European survey - Duncan, Eilidh M.; ten Seldam, Silene; Leleu, Xavier; Loening-Martens, Diane; Pawlyn, Charlotte; Wollenschneider, Séverine; Joyner, Katie; Morgan, Kate (Frontiers in Hematology, 2026)
IntroductionUnderstanding patients’ experiences of treatment and their attitudes towards different options is critical to enabling patient-centered care. There are increasing numbers of myeloma treatments and patient survival has extended. Patients potentially now undergo multiple treatments over the course of their myeloma. Treatment specific factors, such as frequency, location, and mode of administration, along with the burden they place on the patient, may influence treatment decision-making and patients’ quality of life. The aim of this study is to generate evidence on how myeloma patients feel about how, where, and by whom myeloma treatments are administered, and the burden they experience when receiving different treatment types.MethodsAn online survey was developed and translated into seven languages then disseminated through Myeloma Patients Europe’s network of myeloma patient organizations. Eligible participants included people diagnosed with Myeloma, aged over 18 with experience of at least one treatment or were currently receiving their first treatment.ResultsThe survey was completed by 901 patients from 22 countries. Attitudes were most positive for oral treatments at home, yet ‘home-based’ treatment was not universally the most positively rated location. For subcutaneous treatments, out-patient delivery was more positively rated than home-based delivery. Motivation to try new treatments routes was lowest for subcutaneous at home delivered by a relative/friend, and overall highest for oral at home and for delivery through a transdermal patch. Treatment burden was rated highest for intravenous treatments and lowest for oral treatment. The most burdensome domain across all treatment types was the impact on daily activity. Work status was a significant predictor of perceived burden on oral treatment, and age was a significant predictor for oral, subcutaneous and infusion treatment burden.ConclusionsResults suggest that patients may feel uncertain about home-based treatments and patients will need education and support to ensure they feel confident and comfortable. Health care teams need to have transparent conversations with myeloma patients about treatments that include mode, location, and patients’ views, needs and priorities. Patients empowered with knowledge about their potential treatment experience can engage more meaningfully in shared-decision making about their health care.